Does entrepreneurial project monitoring and controlling process matter in social enterprises? Evidence from a developing African country. Issue 1 (January 2023) - Mbiru, James Elvis; Ayentimi, Desmond Tutu; Wickham, Mark
Highlights: Social enterprises are a constituent of the rising 'social and solidarity' economy whose established vision is to create social value and generate positive social outcomes. The paper provides academic and practitioners alike with practical evidence of avenues to incorporate entrepreneurial actions, orientations, and decisions into 'traditional' project management as a business process. Social enterprises in Uganda have demonstrated the capability to nurture corporate strategic renewal, entrepreneurial management and corporate venturing to balance their financial and social value delivery. In a fast-changing and complex environment in developing economies, innovating, and reacting to change by means of corporate entrepreneurship is crucial for social enterprises sustainability. Abstract: Social enterprises in developing countries act as development agents and are a constituent of the rising 'social and solidarity' economy whose established vision is to create social value and generate positive social outcomes. Traditional monitoring limit project managers' capabilities to probe a project's 'known – unknown' impacts. Given that traditional monitoring arrangements persist to be challenging in resolving the high project failure rate in Africa, entrepreneurial project monitoring and controlling process enables project success. Corporate entrepreneurship literature has provided a strong theoretical basis for incorporating entrepreneurial actions, orientations, and decisions into 'traditional' project management process. This paper draws primary data from six selected social enterprises in Uganda to examine what constitute entrepreneurial project monitoring and controlling process. The findings support the need for (a) creating room for errors, (b) self-managed teams, and (c) soft skills maximisation amongst entrepreneurial project managers. Implications for strengthening social entrepreneurship ecosystems in developing economies to accelerate and scale-up social ventures to deliver social and economic value is discussed.